Risk factors for cutaneous malignant melanoma among aircrews and a random sample of the population. Issue 11 (22nd October 2003) - Rafnsson, V; Hrafnkelsson, J; Tulinius, H; Sigurgeirsson, B; Hjaltalin Olafsson, J
Abstract : Aims: To evaluate whether a difference in the prevalence of risk factors for malignant melanoma in a random sample of the population and among pilots and cabin attendants could explain the increased incidence of malignant melanoma which had been found in previous studies of aircrews. Methods: A questionnaire was used to collect information on hair colour, eye colour, freckles, number of naevi, family history of skin cancer and naevi, skin type, history of sunburn, sunbed, all sunscreen use, and number of sunny vacations. Results: The 239 pilots were all males and there were 856 female cabin attendants, which were compared with 454 males and 1464 females of the same age drawn randomly from the general population. The difference in constitutional and behavioural risk factors for malignant melanoma between the aircrews and the population sample was not substantial. The aircrews had more often used sunscreen and had taken more sunny vacations than the other men and women. The predictive values for use of sunscreen were 0.88 for pilots and 0.85 for cabin attendants and the predictive values for sunny vacation were 1.36 and 1.34 respectively. Conclusion: There was no substantial difference between the aircrew and the random sample of the population with respect to prevalence of risk factors for malignant melanoma. Thus it is unlikely that the increased incidence of malignant melanoma found in previous studies of pilots and cabin attendants can be solely explained by excessive sun exposure.